Composite Nanostructures With Metal Components - V.V. Kulish (Журнал нано- та електронної фізики)
The paper provides an overview of the current state of theoretical and experimental investigations of the properties (mainly optical) of composite nanostructures that contain metal components, as well as of small solid metal clusters. The paper describes traditional metal nanoshells and nanotubes as well as more complex nanosystems obtained during recent years – nanorice (ellipsoidal nanoshells), nanoeggs and nanocups (nanoshells with non-concentric core), and multi-layer nanoshells - so-called nanomatryoshkas. In the work, the description of the specific properties of these nanosystems and of the existing approaches to their investigation is given. The main aspects of the technical applications of the composite nanostructures with the metal components are described.